Chapter Dai distretti sociali alle bioregioni urbane - Bonomi, Aldo (Territori, 2023)
At the intersection of economics and sociology, geography and planning, the concept of social district presents unmistakable assonances with that of urban bioregion. Both refer to (and trigger) a return, the former to the social, the latter to the territory; and both presuppose an assumption of consciousness and responsibility, in the management of self-government dynamics, on the part of industrious and cooperating territorial communities, which in this establish themselves as communities of care. The contribution unfolds the intricate and rich yarn of relations between the two perspectives, in which correspondences and discordances, themes and variations interweave together to create a common vision and project.